Warm Ginger Compress for Hypertension Headache : A Case Study - Yuniawati, Yuyun; Puspitasari, Rina (Universitas Pendidikan Indonesia, 2024)
Background : Hypertension is an increase in blood pressure in the arteries, where systolic blood pressure is above 140 mmHg and diastolic blood pressure is above 90 mmHg. In general, when someone suffers from hypertension, signs and symptoms will appear, one of which is head or neck pain. Head or neck pain can interfere with daily activities. One non-pharmacological action to reduce or treat headaches or neck pain is to apply a warm ginger compress. Objective: This study aims to find out the effect of warm compress is the provision of a feeling of warmth in a certain area, where the warm compress given is able to dilate the blood vessels and the oxygen supply becomes smooth and relieves tension, as a result the pain can be reduced. Methods: Data obtained from the results of the study, namely Mrs. M with acute pain problems. Results: After nursing care for 3 days, the scale before administering the warm ginger compress was moderate pain level (scale 5). And after giving a warm ginger compress there was mild pain (scale 2). Conclusion: So it can be concluded that warm ginger compresses are effective in reducing pain in hypertensive patients.